TEKNIK BUDIDAYA JAGUNG (Zea Mayz L) UNTUK MENINGKATKAN HASIL - Wartapa, Agus (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
This study aims The Number of Seeds and Pruning of Maize Yields (Zea mayz L). The research was conducted in April to December in the village of Pandes, Wedi Subdistrict, Klaten Regency, Central Java Province. High land 115 m type soil Vertosol. This research used a completely random factorial 2 x 4 randomized Block design. The First factor is the number of corn seeds per planting hole (B), consisting of 2 levels B1: 1 seed per planting hole with a spasing (column) of 20 cm, B2: 2 seeds per planting hole white a inter spasing (row) 40 cm. The second factor is pruning (P), consisting of 4 levels: P0 white out pruning (control), P1 pruning leaves under the corn cob, P3 pruning male lowers (tassel) and P4 in combination. Results, all treatment parameter had no interaction, except the weight of corn seeds per cob. All treatment parameter was not significantly different except the weight of corn kernels per corn cob. The largest seed weight is the combination of B1P2 (183,93 grams per corn cob, number of seeds 1 grain planting hole with pruning of leaves and male lowers. The smallest seed weight is the combination of B1P0 (176,88 grams per corn cob, number of seeds 1 grain planting hole without pruning.